THE IMPLEMENTATION OF PROBLEM-BASED LEARNING TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Erawanto, Udin; Triantoro, Miranu (JOSAR (Journal of Students Academic Research), 2024)
The research aims to improve students' problem solving and critical thinking skills. The research stages consist of planning, carrying out activities, observing and reflecting. The target students of the 2021/2022 Pancasila and Citizenship Education study program were 22 students, political science courses. The data collection used tests and non-tests. Instruments in the form of observation sheets and esay tests. The data analysis technique is quantitative and qualitative. The results showed an increase in the ability of lecturers from initially good (80.60%) to very good (93%), the ability to solve problems from initially none in the excellent category to none, namely 5%, good category 15%, good enough category 2%, critical thinking ability there was an increase in the percentage of students from none who thought very critically to none by 18.18%, critical thinking 68.18%, thinking quite critically 13.64%.